A Review of Ubiquitous Language Learning Environment - Zurainee Mohd Tahir; Haryani Haron; Jasber Kaur (Institute of Advanced Engineering and Science, 2018)
In today’s era of ubiquitous learning research, various studies have investigated the transformation of ubiquitous learning in multiple aspects. However, most of these research mainly focus on the study of ubiquitous learning environment. Limited review is on the configuration and components of ubiquitous learning focusing on the interaction process in language learning. Hence, this research performed literature analysis for ubiquitous language learning environment whereby it intends at providing specific information about ubiquitous learning concepts and the criteria that needed in the future research focusing on language learning. It begins by briefly describing the concept of ubiquitous learning environment, language learning skills and the importance of vocabulary learning and then on adult language learning. Finally, ubiquitous learning applications for multiple types of language learning are also compared and discussed to further enhance the understanding of ubiquitous language learning environment. Therefore, it is important to have a medium that can be used to improve language learning process to be more interactive. The result will also become a reference point to assist development of ubiquitous language learning applications.